Guidance and Counseling Strategies in Improving Empathy in Junior High School Students - Aprilyaningtiyas, Happy Dyah; Indreswari, Henny; Ramli, M. (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
The phenomenon of declining empathy among adolescents, especially junior high school students, is characterized by low concern and appreciation for others. This study aims to determine the level of empathy of students at State Junior High School 1 Ngantang, so that counselors can develop appropriate service programs to help improve empathy in each student, with the hope of being able to achieve emotional maturity in accordance with the Independence Competency Standards at the junior high school level. The research method used is a descriptive survey with the Basic Empathy Scale (BES) instrument distributed to 60 students of grade VIIII through a purposive sampling technique. The results showed that the level of empathy of students at State Junior High School 1 Ngantang obtained the lowest presentation on the perspective taking indicator (58.33%), and the empathic concern indicator 61.53%. The recommended empathy development strategies include the application of innovative media such as "Our Feelings", modeling techniques, cinematherapy, bibliotherapy, sociodrama, and the integration of local cultural values ​​such as tepa salira. In conclusion, a specific guidance and counseling service program that focuses on the empathy aspect is very necessary to help students achieve optimal emotional maturity according to the Independence Competency Standards at the Junior High School level.